Cultivating global diversity character through culturally responsive and differentiated learning in heterogeneous elementary schools - Uswantun Kasanah; I Nengah Suastika; Desak Putu Parmiti (Psychology, Evaluation, and Technology in Educational Research, 2025)
This qualitative study explores the understanding and challenges of instilling global diversity character through the integration of Culturally Responsive Teaching (CRT) in highly heterogeneous elementary schools. A qualitative approach was employed, with a focus on grade IV students from several private schools in Bali, Indonesia, known for their diverse student demographics. The findings indicate that while students possess a commendable foundation of local tolerance, their internalization of a broader global diversity is largely superficial. This gap is attributed to the lack of pedagogical strategies that explicitly link local understanding to a global context, compounded by the significant internal diversity of students in terms of readiness, interests, and learning profiles. The research reveals that although teachers have attempted to implement CRT, they face challenges primarily due to limited time and resources in comprehensively differentiating content, process, and product to meet these varied needs. This study argues that a synergistic integration of CRT and differentiated learning is crucial to bridge this gap, fostering tolerance and also a genuine and profound understanding, or deep learning, of global diversity that prepares students to be empathetic and adaptable global citizens.